IMPLEMENTASI PENJATUHAN SANKSI ADMINISTRASI TERHADAP PELANGGARAN DISIPLIN PEGAWAI NEGERI SIPIL - Chairul Nopriansyah (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
The main problem of this research is the role and position of the sub-district in the implementation of regional government according to law number 23 of 2014. The problem is then, what is the role and position of the sub-district in implementing regional government according to law number 23 of 2014 and what factors influence leadership camat in implementing its functions, duties, and authority according to law number 23 of 2014. This research is normative legal research that is prescriptive and technical or applied. The research approach uses a legal approach and a case approach. The type of research data is secondary data with primary legal material and secondary legal material. Data collection techniques in the form of library studies and data analysis techniques used are deductive. The results of this study explain that the Role and Position of the Sub-District Head in the implementation of regional government according to Law Number 23 of 2014, namely the Sub-District is no longer a unit of governmental territory, but as a unit of work or service area. The status of the sub-district is now a district / city apparatus that is equivalent to the regional offices and technical institutions, even the kelurahan. The sub-district head accepts delegation as the authority of the Regent / Mayor to handle it as a matter of regional autonomy (delegative authority), the Camat also carries out the general duties of the government in accordance with Law Number 23 Year 2014 (Attributive authority). The sub-district was formed as the implementing principle of decentralization.